Severe Malaria with a Rare Tetrad of Blackwater Fever, Acute Renal Failure, Disseminated Intravascular Coagulopathy, and Acute Acalculous Cholecystitis - Hira Hanif; Biraj Shrestha; Salina Munankami; Manish Shrestha; Bidhya Poudel; Roopika Reddy; Syed Jaleel; Debra Powell (Case Reports in Infectious Diseases)
Background. Blackwater fever (BWF) is a severe clinical syndrome occurring as a complication of malarial infection characterized by intravascular hemolysis, hemoglobinuria, and acute renal failure in people exposed to Plasmodium falciparum and, to some extent, in people who were exposed to medications like quinine and mefloquine. The exact pathogenesis of classic BWF remains unclear. The mechanism leading to damage to the red blood cells (RBCs) can be immunologic nonimmunologic, leading to massive intravascular hemolysis. Case Presentation. We present a case of classic blackwater fever in a 24-year-old otherwise previously healthy male without any history of antimalarial prophylaxis use, returning from recent travel to Sierra Leone. He was detected to have P. falciparum malaria in the peripheral smear test. He was treated with artemether/lumefantrine combination therapy. Unfortunately, his presentation was complicated by renal failure and was managed with plasmapheresis and renal replacement therapy. Conclusion. Malaria continues to be a parasitic disease that can have devastating effects and continues to be a challenge globally. Although cases of malaria in the United States are rare and cases of severe malaria, mainly attributed to P. falciparum, are even more uncommon. Care should be taken to retain a high level of suspicion to consider the diagnosis, especially in returning travelers from endemic areas.